2003
DOI: 10.1007/s00264-003-0459-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for large and massive tears of the rotator cuff

Abstract: Patients with a large or massive tear of the rotator cuff were, when possible, treated with the McLaughlin procedure. A patch graft was used when it was impossible to perform this procedure. The patch group (group P) consisted of nine patients with nine shoulders (six men, three women) with a mean age of 62.8±6.9 years. The McLaughlin group (group M) consisted of 12 patients with 12 shoulders (ten men, two women) with a mean age of 52.3±8.6 years. Mean follow-up was 2 years 11 months in group P and 4 years 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Ito and Morioka in their study in 2003, [14] also commented that decreased re-tearing noted on the McLaughlin patch graft group compared to the regular McLaughlin group may be in part due to decreased tension allowed by the patch graft re-enforcement of the primary cuff repair. [14] Comment The senior author continues to use patch grafts in both frail tissue repairs as well as large cuff defects in paraplegic and non-paraplegic patients. The current graft of choice is a dermal allograft (see Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Ito and Morioka in their study in 2003, [14] also commented that decreased re-tearing noted on the McLaughlin patch graft group compared to the regular McLaughlin group may be in part due to decreased tension allowed by the patch graft re-enforcement of the primary cuff repair. [14] Comment The senior author continues to use patch grafts in both frail tissue repairs as well as large cuff defects in paraplegic and non-paraplegic patients. The current graft of choice is a dermal allograft (see Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Bond et al [13] found 13 of 16 patients had MRI confirmed integration and overall patient satisfaction with the augmentation of irreparable RC tears with GraftJacket Allograft with 2 year average follow-up. One Japanese study by Ito and Morioka [14] compared the McLaughlin procedure alone (n = 12) to repair using a double layer allograft patch (n = 9). The McLaughlin procedure described in that article begins with a deltoid split and is essentially a trans-osseous non-tension repair of deficient cuff which clears the articular surface of the humeral head into a trough cut into the medial aspect of the GT just lateral to the humeral head articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to decrease the failure rate and improve the outcomes of massive cuff tears repair, the use of patch grafts was introduced and popularized by various authors. Many varieties of patch materials have been developed and used clinically, including synthetic materials Polyester ligament (Dacron) [100], Gore-Tex soft tissue patch [101], Mersilene mesh [102], Teflon felt [103] and Carbon fibrebre patches [104], allografts freeze*dried rotator cuff [105,106], quadriceps tendon [107], patellar tendon, achilles tendon [107], dermal matrix (Graftjacket) [107], tensor fascia late [108] and xenografts porcine dermal collagen [109,110], porcine small intestinal submucosa [111]. Autografts such as the biceps tendon [112,113] and tensor fascia late [114] have also been used.…”
Section: Rotator Cuff Repair With Patchmentioning
confidence: 99%